UI/UX Gamification Features in Campaign Application Using Design Thinking Method - Alami, Almira Zavira; Mardiana; Trisya Septiana (Journal of Engineering and Scientific Research, 2023)
During the Covid-19 pandemic that hit all corners of the world, many people had to change their daily lives and one of them was social activities. Campaign is a mobile-based application to carry out social actions and open donations from sponsors where users can take part in campaign actions anywhere and anytime and also make donations without having to spend a penny. The problem experienced by Campaign is that users don’t do challenge actions on a regular basis because this action takes several days, so users often lose motivation in the middle of the road and the challenges are not completed. Based on the problems, the gamification feature was designed to motivate users in completing challenges. The design of this gamification feature uses the Design Thinking method which passes through 5 stages, which are Empathize, Define, Ideate, Prototype, Test. The result of this research is a prototype of the gamification feature which is designed with three iterations of changes and testing of the prototype is carried out to get UI/UX design results that are in line with the main goal. The test results on three informants were passed with an average SEQ score of 6.57 from a scale of 1-7. There are several elements, such as the system level and badges, that need to be developed in the design iteration so that the UI design results of the gamification feature are more ready to use.